The Effects of Quercetinon Interleuikin (IL-8) Serum, %Forced Expiratory Volume in One Second (FEV1), and COPD Assessment Test (CAT) Scores in Stable Chronic Obstructive Pulmonary Disease (COPD) Patients - Maratus Sholihah; Suradi Suradi; Jatu Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Introduction: Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality worldwide. Cigarette smoke and noxious agent result in oxidative stress and activate release of inflammatory mediators such as Interleukin-8 (IL-8). Quercetin is a flavonoid compound containing anti-inflammatory effects which can be used as an adjuvant therapy in stable COPD. Objective: To analyze the effect of quercetin on serum IL-8 levels, % VEP1, and CAT score of stable COPD patients. Methods: Experimental clinical trial with pre-test and pasca-test design was performed in 30 patients with stable COPD in Dr. Moewardi Surakarta between December 2017 and January 2018. The samples taken by using purposive sampling were divided into two groups treatment groups received standard therapy and quercetin 500mg/day for 28 days and control groups only received standard therapy. The decrease in inflammation was measured by serum IL-8 examination, improvement of obstruction measured by %FEV1 and clinical improvement measured by CAT score. Results: IL-8 serum level was significantly lower in treatment group than of in control group (p=0,001). The percentage of FEV1 was insignificant different between the two group (p=0,236). However CAT score was significantly lower in treatment group compared to that of in control group (p=0,001) Conclusions: Quercetin can decrease IL-8 serum level and decrease CAT score when given in combination with standard therapy for COPD patients. (J Respir Indo 2019; 39(2): 103-12)